An 8-week exergame-based exercise training program improves cardiovascular endurance, muscular strength and endurance performances among primary school children in Taiwan - Lin, Chi-Fang; Lee, Po-Fu; Su, Yan-Jhu; Lin, I-Tung; Kao, Hsiao-Fang; Hung, Yi-Chuan; Chao, Mei-Ling; Ho, Chien-Chang (Frontiers in Pediatrics, 2025)
ObjectivesThe aim of the present study was to determine the effects of an 8-week exergame-based exercise training program on health-related physical fitness performances among primary school children in Taiwan.Materials and methodsThe study employed a randomized controlled trial (RCT) design, recruiting 68 elementary school children with an average age of 10.76 ± 0.49 years. Participants were randomly divided into an experimental group (n = 35) and a control group (n = 33). The experimental group completed an 8-week exergame-based exercise training program, performed three times per week. Each session consisted of three one-minute rounds. In contrast, the control group did not undergo any training and continued their usual daily activities. Data collection included demographic surveys, anthropometric assessments, and health-related physical fitness evaluations conducted at baseline (Week 0) and after the intervention (week 8).ResultsAfter the 8-week exergame-based exercise training program, the results indicated that compared to the control group, the experimental group significantly reduced their 800-m run time [β = −21.771, p = 0.005 (enhanced cardiovascular endurance)] and increased their performance in bent-leg sit-ups [β = 4.036, p = 0.021 (muscular strength and endurance)] after adjusting for age, gender, and other health-related physical fitness indicators.ConclusionThis suggests that 8-week exergame-based exercise training program can be a fun exercise alternative for improving cardiovascular endurance, muscular strength and endurance performances among primary school children in Taiwan.